Taste and power : furnishing Modern France - Auslander, Leora (Studies on the history of society and culture ;, 1996)
Enlivened and enriched by Auslander's experiences as a cabinetmaker, this pathbreaking work demonstrates that in post-Revolutionary France, furniture and consumer goods became newly important means of constituting selves, social class, and, perhaps most significantly, the economy and society of the nation itself. The very style of the goods reflected these preoccupations: nineteenth-century bourgeois style was dominated by gendered versions of Old Regime-style furniture, while the working class was offered new furniture designed specifically for its needs. Tastemaking took on a sudden urgency, reflected in the creation of new schools, museums, expositions, libraries, magazines, and books designed to "improve" the taste of producers and consumers alike. As these institutions competed with furniture sellers, a fierce competition sprang up among government bureaucrats, private philanthropists, and distributors to control workers' and consumers' taste. Auslander melds the history of high politics - the formation of the state - with the history of the mundane - furniture - in order to examine how power was consolidated, reproduced, and even resisted in the small objects and gestures of everyday life in France